Cálculo de los factores de industrialización, productividad y calidad del clúster agroindustrial de la quinua en el departamento del Cauca (2019)
this project study was carried out using the SANDAG methodology of the main factors the agroindustrial cluster of quinoa in the Cauca department, in order to determine the cluster industrialization potential and this allows generating an endogenous development in the cluster´s influence area. In order to determine cluster´s potential, the actors characterization is necessary. This characterization was carried out through a quantitative analysis of characteristics of companies that make up this cluster. In addition to the main sectors that make up and influence the production chain of quinoa in the department of Cauca, in order to determine the outlook of the chain, the needs and challenges that must overcome to generate competitiveness not only at the national level, but internationally and most importantly with products with high added value in such a way that they constitute a competitive advantage in the world.